Controles prenatales y su asociación con la morbimortalidad del recién nacido en el hospital Sergio Bernales, enero – mayo 2016: Prenatal controls and its association with the morbimortality of the newborn in the hospital Sergio Bernales, january - may 2016 - Lozano-Ventura, Oscar A. (2022)
Abstract   Objective: To determine the association between prenatal controls and morbidity and mortality in the newborn at the Sergio Bernales hospital, January-May 2016. Methods: Quantitative, observational, analyticrelational, retrospective study. The population was formed by 2350 newborns. The sex, gestational age, weight, morbidity and mortality variables of newborns recorded in the registry of births of the neonatology service were studied, a data collection form was used. Results: We proceeded to use the Chi-square statistic to find the association between the variables, obtaining a p = 0.000 (value less than 0.05), which indicated that such an association exists. In relation to the morbidity and mortality of newborns with less than 6 prenatal controls, an OR = 52,305 (95% CI: 40,786 -67,077) and OR = 8,175 (95% CI: 6,269 -10,661) were obtained, being statistically significant. Conclusion: There is a significant association between the prenatal controls and the morbidity and mortality of the newborn. Key words: Prenatal control; Morbidity; Mortality; Newborns; Birth weight. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1267